Ethnic-Cultural Bullying - Rio Kurniawan; Safutra Rantona; Yuni Dahlia Yosepha Mogot; Vidya Nindhita (Universitas Nusa Cendana, 2026)
This study aims to examine how SARA-related discourse targeting the Madurese ethnic group is produced and normalized through digital interactions on the Instagram account @fuadsasmitaa. Employing a qualitative approach within a constructivist paradigm, this research applies netnography as the primary method. Data were collected through virtual observation and documentation of 20 highly engaged posts and their comment sections. The data were analyzed using thematic analysis to identify patterns of discourse, audience responses, and mechanisms underlying the normalization of ethnic-based bullying. The findings reveal that humorous content, although not explicitly conveying SARA-related messages, encourages audiences to generate derogatory comments toward the Madurese ethnic group. Repeated interactions between content and audience responses contribute to the normalization of ethnic-cultural bullying in digital spaces, reinforcing psychological stigmatization and ethnic polarization among social media users.